Functional and Structural Brain Plasticity in Adult Onset Single-Sided Deafness - Shang, Yingying; Hinkley, Leighton B.; Cai, Chang; Subramaniam, Karuna; Chang, Yi-Shin; Owen, Julia P.; Garrett, Coleman; Mizuiri, Danielle; Mukherjee, Pratik; Nagarajan, Srikantan S.; Cheung, Steven W. (Frontiers in Human Neuroscience, 2018)
Single-sided deafness (SSD) or profound unilateral hearing loss obligates the only serviceable ear to capture all acoustic information. This loss of binaural function taxes cognitive resources for accurate listening performance, especially under adverse environments or challenging tasks. We hypothesized that adults with SSD would manifest both functional and structural brain plasticity compared to controls with normal binaural hearing. We evaluated functional alterations using magnetoencephalographic imaging (MEGI) of brain activation during performance of a moderately difficult auditory syllable sequence reproduction task and assessed structural integrity using diffusion tensor magnetic resonance imaging (DTI). MEGI showed the SSD cohort to have increased induced oscillations in the theta band over the left superior temporal cortex and decreased induced gamma band oscillations over the frontal and parietal cortices between 175-475 ms following stimulus onset. DTI showed the SSD cohort to have extensive fractional anisotropy reduction in both auditory and non-auditory tracts and regions. Overlaying functional and structural changes revealed by the two imaging techniques demonstrated close registration of cortical areas and white matter tracts that expressed brain plasticity. Hence, complete loss of input from one ear in adulthood triggers both functional and structural alterations to dorsal temporal and frontal-parietal areas.